Hierarchically porous 3D-printed akermanite scaffolds from silicones and engineered fillers. Issue 14 (November 2019) - Dasan, Arish; Elsayed, Hamada; Kraxner, Jozef; Galusek, Dusan; Bernardo, Enrico
Abstract: The present investigation is dedicated to the manufacturing of reticulated three-dimensional akermanite scaffolds, developed by direct reaction between silica, from the oxidation of a commercial silicone resin and oxide fillers, forming pastes for direct ink writing. Crack-free scaffolds, with dense and regular struts, were due to the use of CaCO3 (micro) and MgO nano-particles as reactive fillers. An excellent phase purity was obtained, with the help of the liquid phase provided by anhydrous sodium borate (Na2 B4 O7 ), upon firing. The structure of the scaffolds, finally, was successfully modified by using Mg(OH)2 and hydrated sodium borate: besides macro-porosity from direct ink writing, the new scaffolds exhibited homogenous 'spongy' struts (owing to water vapor release in the heating step), with no crack. Both types of scaffolds (with dense or porous struts) exhibited remarkable strength-to-density ratios.